Legge del valore, legge dello scambio e problema della trasformazione: una nota - Giancarlo Gozzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
– Marx's analysis of the determination of the general rate of profit and of the associated relative prices is based on the conceptual distinction between law of value and law of exchange. The law of value states that simple, necessary abstract labour is the substance and measure of the value of commodities and is fundamental in the analysis of the social relations of the capitalist economy, i.e. for the analysis of the creation of surplus-value; it therefore represents the theoretical framework within which the problem of the distribution of surplus-value among the different capitals may be approached, i.e. the law of exchange must be taken into consideration. The analytical mistakes surrounding the marxian solution of the problem have given the way to the critics of the labour theory of value to question its relevance and coherence as a tool for the analysis of the capitalist mode of production. The aim of the present note is simply to show that it is possible to frame the relationship between law of value and law of exchange along marxian lines while determining in a coherent way the rate of profit and the corresponding relative prices of commodities in such a way that the proportionality between profits and surplus-labour is retained. Actually this is the main result of the "New Interpretation" of the marxian transformation problem which is obtained by defining the conservation of value in terms of the net product and not the gross one and the value of labour power in terms of generalized (or unallocated) purchasing power. This interpretation of the problem is therefore in contrast with the neoricardian one which is based on the refutation of the role of the law of value different from that of the determination of the relative prices of the commodities.
Keywords: B14; B24; B51; 330